Ovarian Dysgerminoma with Metastases in Supraclavicular Lymph Nodes Diagnosed in a 16-year-old Girl: Clinical Case and Literature Review - Maldžiūtė, Diana; Rukauskaitė, Vilma; Trainavičius, Kęstutis (Lietuvos chirurgija, 2018)
[full article, abstract in English; abstract in Lithuanian]BackgroundTumors of children reproductive system are rare, the most frequent among them is ovarian tumor. The most frequent histological type of ovarian tumor in girls and adolescents is germ cell tumor, with dysgerminoma being the most frequent of all. Symptoms are very non-specific, this is why these tumors are often diagnosed late. Dysgerminoma is a malignant tumor, thus if not treated, it may be potentially lethal.Case reportWe present a 16-year old patient, who has come to Vilnius University Hospital Santaros Klinikos, Children’s unit, due to a sudden emergence of a growth above the left clavicle. The girl did not have any other specific complaints. Huge hard growth was founded during palpation of the abdomen. After the cancer marker test (alfa-fetoprotein – 1,9 kU/L, beta-human chorionic gonadotropin – 1231.0 U/L; lactate dehydrogenase – 2721.0 U/L; Ca125 – 665.8 kU/L), pelvic ultrasound examination, computed tomography and histological evaluation of the supraclavicular mass, dysgerminoma of the right ovary FIGO stage IV was diagnosed. The patient was treated with laparotomic oophorectomy and chemotherapy before and after surgery. Treatment was successful as 100% of tumor cells necrosis was achieved.ConclusionsGirls and adolescents should be suspect to ovarian masses if they complains about abdominal pain, a growth in the abdominal area, disruptions of menstrual cycle or signs of premature puberty. Early diagnosis and treatment of ovarian dysgerminoma have a very good recovery rate in girls and adolescent.
Keywords: ovarian tumors in girls and adolescents, malignant germ cell tumors, dysgerminoma, nonepithelial tumors